Prevalence, associated risk factors and species identification of lung worm infection in sheep in Dangla district, Western Amhara, North West Ethiopia - Dessalew Habte; Ananiya Simeneh (International Journal of Veterinary Science and Research - Peertechz Publications, 2019)
Cross-sectional study was conducted from November 2014 to May 2015 to determine lungworm prevalence, risk factors associated with lungworm infection and identifi cation of species of lungworm in sheep in Dangla district, Northwestern Ethiopia.